Implementasi Etika Bisnis Islam dan Dampaknya Terhadap Budaya Kerja Karyawan di BMT UAS Senori Kabupaten Tuban - Luluk Lutfiyatul Inayah (Journal of Islamic Banking, 2021)
This research aimed to determine the implementation of Islamic business ethics and their impact on the work culture of BMT UAS Senori employees. The approach used was a qualitative approach where researchers conduct observations, interviews, documentation, and data collection by jumping directly into the field. The results showed that Islamic business ethics was well accepted by BMT UAS Senori employees. Islamic business ethics has also been applied in bussines practices by BMT UAS Senori employees, like being fair to the customer, and friendly to the customer. The interviewees also realized the importance of ethics in business, so Islamic business ethics can be implemented in all business activities. Thus, the implementation of Islamic business ethics still needs to be expanded again, involving all levels of society, not just the employees of a company. And the impact obtained when implementing Islamic business ethics that is always maintaining the behaviors, actions, actions when they are working and dealing directly with their customers, always maintaining trust and obeying the rules that exist in a structural organization.